On sequences of contractive mappings and their fixed points - M. Imdad; M. S. Khan; S. Sessa (International Journal of Mathematics and Mathematical Sciences)
By using a condition of Reich, we establish two fixed point theorems concerning sequences of contractive mappings and their fixed points. A suitable example is also given.